Secure Image Transmission in Wireless Sensor Network (WSN) Applications - Shankar, K.; Elhoseny, Mohamed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers an essential guide to Wireless Sensor Networks, IoT Security, Image Processing, Secure Information Systems, and Data Encryption. In addition, it introduces students and aspiring practitioners to the subject of destination marketing in a structured manner. It is chiefly intended for researcher students in the areas of Wireless Sensor Networks and Secure Data Communication (including image encryption, and intrusion detection systems), academics at universities and colleges, IT professionals, policymakers and legislators. Given its content, the book can be used as a reference text for both undergraduate and graduate studies, in courses on Wireless Sensor Networks, Secure Image Processing, and Data Encryption applications. The book is written in plain and easy-to-follow language and explains each main concept the first time it appears, helping readers with no prior background in the field. As such, it is a "must-read" guide to the subject matter.
Introduction -- An Optimal Light Weight Cryptography - SIMON Block Cipher for Secure Image Transmission in Wireless Sensor Networks -- An Optimal Lightweight RECTANGLE Block Cipher for Secure Image Transmission in Wireless Sensor Networks -- An Optimal Lightweight Cryptographic Hash Function for Secure Image Transmission in Wireless Sensor Networks -- An Optimal Haar Wavelet with Light Weight Cryptography based Secret Data Hiding on Digital Images in Wireless Sensor Networks.
Keywords: Wireless communication systems; Mobile communication systems; Computational intelligence; Wireless and Mobile Communication; Computational Intelligence